Quantitative and functional posttranslational modification proteomics reveals that TREPH1 plays a role in plant touch-delayed bolting - Wang, Kai (Proc Natl Acad Sci U S A, 2018)
Environmental mechanical forces, such as wind and touch, trigger gene-expression regulation and developmental changes, called “thigmomorphogenesis,” in plants, demonstrating the ability of plants to perceive such stimuli. In Arabidopsis, a major thigmomorphogenetic response is delayed bolting, i.e., emergence of the flowering stem. The signaling components responsible for mechanotransduction of the touch response are largely unknown. Here, we performed a high-throughput SILIA (stable isotope labeling in Arabidopsis)-based quantitative phosphoproteomics analysis to profile changes in protein phosphorylation resulting from 40 seconds of force stimulation in Arabidopsis thaliana. Of the 24 touch-responsive phosphopeptides identified, many were derived from kinases, phosphatases, cytoskeleton proteins, membrane proteins, and ion transporters. In addition, the previously uncharacterized protein TOUCH-REGULATED PHOSPHOPROTEIN1 (TREPH1) became rapidly phosphorylated in touch-stimulated plants, as confirmed by immunoblots. TREPH1 fractionates as a soluble protein and is shown to be required for the touch-induced delay of bolting and gene-expression changes. Furthermore, a nonphosphorylatable site-specific isoform of TREPH1 (S625A) failed to restore touch-induced flowering delay of treph1-1, indicating the necessity of S625 for TREPH1 function and providing evidence consistent with the possible functional relevance of the touch-regulated TREPH1 phosphorylation. Taken together, these findings identify a phosphoprotein player in Arabidopsis thigmomorphogenesis regulation and provide evidence that TREPH1 and its touch-induced phosphorylation may play a role in touch-induced bolting delay, a major component of thigmomorphogenesis.